Dark currents : agents of Hel - Carey, Jacqueline, 1964- (Carey, Jacqueline, 1964- Agent of Hel., 2012)
"Small town Pemkowet, Mich., is a popular tourist destination for humans. It's also home to a thriving 'eldritch community' of supernatural entities, thanks to the presence of the local underworld controlled by the Norse goddess Hel. Daisy Johanssen, a half-demon trying to dodge her innate attraction to the 'Seven Deadlies' while functioning as Hel's agent on Earth and the local link between the eldritch community and the human police, is called in to help investigate the drowning of a local college boy when signs of both foul play and magical residue are found on the body."